LAPAROSCOPIC PLASTIC WITH PRIMARY STRICTURES OF THE URETEROPELVIC SEGMENT - N. V. Polyakov; N. G. Keshishev; M. V. Gurbanov; M. V. Grigoryeva; L. D. Arustamov; A. V. Kazachenko; B. Ya. Alekseev (Исследования и практика в медицине)
Determination of indications for performing reconstructive and plastic surgical interventions in stricture of UPS is a difficult task. When making an incorrect decision, the treatment can be ineffective. Functional and anatomical preservation of the kidney can significantly affect the outcome of the operation.Purpose. Evaluation of the effectiveness of laparoscopic plastic surgery of stricture of UPS, depending on the anatomical and functional state of the ipsilateral kidney.Material and method. The results of treatment of 134 patients, who underwent for the period from 2012 to 2015 the different types of reconstructive surgical interventions for stricture of the pelvic-ureteral segment (Calp de Virde scrappy plastic surgery, Andersen-Heinz ureteropyelanastomosis, and antineoplastic ureteropyeloanastomosis), were analyzed. To analyze the effectiveness of the treatment, in the preand postoperative period, the following parameters were evaluated: the presence of pain syndrome, the presence of pyeloectasia, the functional state of the renal parenchyma (according to radioisotope renography), and the absence of recurrence of the UPS stricture.Result. The overall efficacy of laparoscopic UPS reconstruction was 94.7%. The results of treatment did not depend on the chosen technique of operative intervention. In this case, the effectiveness of the treatment was dependent on the initial deficiency of kidney function: the best results were seen in patients with kidney function deficiency of less than 25%, and the proportion of ineffective interventions was highest among patients with a deficit of more than 75%. The degree of dilatation of the pelvis in the postoperative period was also associated with preoperative indicators of kidney function deficiency, this may be due to the presence of cup-pelvis-plating system atony.Conclusion. Thus, the results of our work demonstrated the high efficiency of laparoscopic plastics of UPS. The effective- ness of treatment is determined by the timeliness of the intervention. As a basic prognostic criterion for the effective- ness of the forthcoming intervention, the degree of deficiency of the kidney function should be considered.